Industrialização, meio ambiente e consumo: é possível conciliar? - Passarelli, Rosana Pereira (2016)
Intention of this work is answering the initial question about the possibility to reconcile the factors: industrialization, environment and consumption to meet the needs of current society with the economic exploitation of the environment in face of the demands of contemporary society regarding consumption. Through of deductive method and by theorical research we intend to verify bibliographic under the focus of the legislation, with the analysis of the National Politics of the Environment, the Consumer Defense Code, and the article 170 and sections of the Federal Constitution of 1988; in addition to specific legislation, if there is the possibility of harmonious coexistence of such factors, responding at the end, the initial question, assuming that the initial consumption demands of contemporary society dictate the pace for industrial production by moving all the production processes that the end will impact on the environment.